The influence of the professional's gender in the periodicity of Pap Test - doi:10.5020/18061230.2010.p181 - Luis Rafael Leite Sampaio; Maria Albertina Rocha Diógenes; Maria Albertina Rocha Diógenes; Roberta Jeane Bezerra Jorge; Roberta Jeane Bezerra Jorge; Francisco Antonio da Cruz Mendonça; Francisco Antonio da Cruz Mendonça; Lucijane Leite Sampaio; Lucijane Leite Sampaio (Universidade de Fortaleza, 2012)
Methods: A descriptive study, with a qualitative approach, held in the period of September to November, 2008 with 83 users of the Family Health Strategy of Caio Prado, Itapiúna-Ceará, who had Pap test in delay. The data were collected through a semi-structured interview and organized according to the Content Analysis: (1) Professional gender and the periodicity of Pap test and (2) Test that causes pain and fear. Results: It was observed that 67 (80.72%) were between 25 and 59 years, 52 (62.62%) were married, 65 (78.31%) had primary education, 45 (54.22%) were farmers and 49 (59.04%) earned less than minimum wage. Most users reported feelings of shame by male examiners as a reason for irregularity in the frequency of Pap test. On a smaller scale, the reason pointed out was to consider this a test that causes pain and fear. Final Considerations: The users reported that the presence of a male professional was a strong influence to irregularity in the frequency of Pap test in this health unit. Albeit to a lesser extent, prior negative experience with this exam and not the professional's gender issue has been implicated as a reason not to perform periodic cytology.